CRITICAL THINKING IN TEACHING WRITING BOOK REVIEW - Areni, Galuh Kirana Dwi; Syafri, Frimadhona (Language Circle: Journal of Language and Literature, 2015)
Critical thinking is important in university because students can have some benefits e.g. (1) achieving better marks; (2) reducing their dependency on teachers and text books; and (3) creating their knowledge. Therefore, students are supposed to be able to apply critical thinking skills to all their academic reading, writing, listening and discussing. Book Report and Review is one of the subjects taught in English Department of Unnes. Writing book reviews is not only informational, but also analytic and persuasive. In doing it, consequently, students are required to have critical thinking skills in analysing the content, format, argument, and context to argue that the book is worth reading or not. In order to display critical thinking, they need to develop skills in interpreting, analysing, reasoning, and evaluating. This presentation will focus on how to develop teaching strategies that can foster students' critical thinking in writing book reviews. It will discuss the concept of critical thinking for undergraduate students, its implementation in teaching writing book reviews, and its assessment in students' book review writing texts.